2017
DOI: 10.1016/j.still.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Soil structure changes induced by tillage systems

Abstract: Structure represents one of the main soil physical attributes indicators. The soil porous system (SPS) is directly linked to the soil structure. Water retention, movement, root development, gas diffusion and the conditions for all soil biota are related to the SPS. Studies about the influence of tillage systems in the soil structure are important to evaluate their impact in the soil quality. This paper deals with a detailed analysis of changes in the soil structure induced by conventional (CT) and no-tillage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
119
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(138 citation statements)
references
References 63 publications
13
119
0
6
Order By: Relevance
“…Nevertheless, even with higher soil compaction and similar porosity, GC doubled the infiltration rates of T. The vegetation cover, penetration resistance and infiltration scored similarly in the canonical analysis indicated that the soil compaction itself is no enough to explain the water movement in the soil. Our results agree with those from Pires et al (2017) and Gao et al (2017) which observed small differences in macroporosity, but a better pore connectivity under no tillage treatment. Thus, despite soil compaction, GC improves the water movement while not threatening the soil aeration.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, even with higher soil compaction and similar porosity, GC doubled the infiltration rates of T. The vegetation cover, penetration resistance and infiltration scored similarly in the canonical analysis indicated that the soil compaction itself is no enough to explain the water movement in the soil. Our results agree with those from Pires et al (2017) and Gao et al (2017) which observed small differences in macroporosity, but a better pore connectivity under no tillage treatment. Thus, despite soil compaction, GC improves the water movement while not threatening the soil aeration.…”
Section: Discussionsupporting
confidence: 92%
“…GC showed low impact on soil porosity. Slight differences were observed for WHC, macro, meso, micro and total porosity and only WHC and microporosity had significant differences between CB and T. Nevertheless, GC infiltration rates doubled T. Therefore, the improvement in soil structure of GC created a new pore system with a better connectivity as other researchers found (Gao et al, 2017;Pires et al, 2017). This improvement represents a greater use of rainwater and, therefore, of water economy.…”
Section: Gc Influence On Soil Parametersmentioning
confidence: 81%
“…The soil inside the wooden beds was submitted to four regimes of soil water content (35,28,21 and 14% at volumetric basis). The treatments (cultivars and water regimes) were allotted completely randomized in a 2×4 factorial experiment with 4 replications.…”
Section: Methodsmentioning
confidence: 99%
“…La densidad aparente baja, alta capacidad de retención de humedad y altos contenidos de amorfos y materia orgánica son comunes en Andosols (IUSS Working Group WRB, 2015); sin embargo, éstas propiedades pueden sufrir cambios irreversibles (McDaniel et al, 2012), por eliminación de la cubierta vegetal o por los diferentes sistemas de labranza. Pires et al (2017) reportaron que la porosidad total puede disminuir hasta 40% (0 a 30 cm de profundidad) de suelos sin labranza a suelos con labranza tradicional.…”
Section: Figura 2 Desarrollo Estructural De Andosols Bajo Bmm A) Y unclassified